Fusions. Les démarches symbiotiques de Marta Pan et André Wogenscky - Dominique Amouroux (In Situ)
Marta Pan, a Hungarian-born sculptor, and André Wogenscky, an architect well known for having designed some of the most successful public buildings during the 1960s and 1970s, seem to have succeeded in avoiding a situation deplored by Viollet-le-Duc. In his 1893 book De la décoration appliquée aux édifices, he deplored ‘The painter thought of his painting without worrying about what surrounded it. The sculptor had no other idea than to attract attention to his work, even if he roughly elbowed the architect and effaced the painter’. This situation still prevailed in the 1960s when the integration of works of art into public buildings – the famous 1% – is often called ‘decoration’ although the programme aimed at a convergence of disciplines. Marta Pan and André Wogenscky went further then in the fusion of their creations, merging their practices thanks to their shared conviction as to the importance of space for man, and the indispensable tension in space affirming all the qualities that the designer intends to give it. From 1952 to the early 2000s, their constructions and interventions in urban spaces illustrate this practice which was carefully thought through.